Clinical Guideline Highlights for the Hospitalist: Secondary Fracture Prevention for Hospitalized Patients. Issue 2 (20th January 2021) - Siau, Evan; Harrington, Matthew; Steinberg, Daniel; Burger, Alfred
Abstract : GUIDELINE TITLE: Secondary Fracture Prevention: Consensus Clinical Recommendations from a Multistakeholder Coalition RELEASE DATE: September 20, 2019 PRIOR VERSION: Not applicable DEVELOPER: American Society for Bone and Mineral Research Task Force and Multistakeholder Coalition FUNDING SOURCE: American Society for Bone and Mineral Research and the Center for Medical Technology Policy TARGET POPULATION: Adults 65 years or older with a hip or vertebral fracture. This review will focus on the core recommendations and their application in the practice of hospital medicine.